The impact of alignment (strategy / structure) on organizational effectiveness in the organization. A case study of a sample of Algerian institutions - fatima Bouhelal; Lakhder Adouka (Dirassat Journal Economic Issue, 2016)
The objective of this study is to examine the impact of compatibility (strategy / structure) on organizational effectiveness in the organization. According to the empirical study, we found that there is a positive relationship between compatibility (strategy / structure) and organizational effectiveness and that the absence of such a consensus would lead to poor performance on the sample companies in our study